READING MODELS OF STUDENTS WITH DIFFERENT READING HABIT AND ATTITUDE TOWARDS READING - Magdalena Br. Marpaung (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2021)
ABSTRACT Based on readers’ perspective reading process is affected by reading habit and the attitude towards reading (Marpaung, M. 2021). Further, due to find the most related factor in second language reading habit, there were three factors compared of first language reading habit, attitude towards reading, and language proficiency, and it was found that language proficiency is mostly affected the second language reading habit (Marpaung, M. 2020). Therefore, there is a willing to know the contribution of reading habit and attitue towards reading in reading cognitive processes. And by administered the close interview it was found that reading habit and attitude towards reading affected cognitive model of reading in its term of schemata activation and handling new and difficult words, it was also mainly affected in finalizing the comprehension of doing concluding or summarizing.